Comprehensive Analysis of Long Non-coding RNA and mRNA Transcriptomes Related to Hypoxia Adaptation in Tibetan Sheep - Lu, Zengkui; Yuan, Chao; Li, Jianye; Guo, Tingting; Yue, Yaojing; Niu, Chune; Liu, Jianbin; Yang, Bohui (Frontiers in Veterinary Science, 2022)
Tibetan sheep have lived on the Qinghai-Tibet Plateau for a long time, and after long-term natural selection, they have shown stable genetic adaptability to high-altitude environments. However, little is known about the molecular mechanisms of the long noncoding (lnc)RNAs involved in the adaptation of Tibetan sheep to hypoxia. Here, we collected lung tissues from high-altitude Tibetan sheep and low-altitude Hu sheep for RNA sequencing to study the regulatory mechanisms of the lncRNAs and mRNAs in the adaptation of Tibetan sheep to hypoxia. We identified 312 differentially expressed lncRNAs and 1492 differentially expressed mRNAs. We found 28 pairs of cis-regulatory relationships between 23 differentially expressed lncRNAs and 20 protein-coding genes and two pairs of trans-regulatory relationships between two differentially expressed lncRNAs and two protein-coding genes. These differentially expressed mRNAs and lncRNA target genes were mainly enriched in pathways related to lipid metabolism and immune function. Interaction network analysis showed that 25 differentially expressed lncRNAs and 22 differentially expressed mRNAs had an interactive relationship. Additionally, we used six differentially expressed lncRNAs and mRNAs to verify the accuracy of the sequencing data via qRT-PCR. Our results provide a comprehensive overview of the expression patterns of the lncRNAs and mRNAs involved in the adaptation of Tibetan sheep to hypoxia, laying a foundation for further analysis of the adaptations of plateau animals.